2019
DOI: 10.1039/c8nr07730d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based drug delivery via RBC-hitchhiking for the inhibition of lung metastases growth

Abstract: RBC-hitchhiking regime is shown without prolongation of nanoparticle blood circulation but with the record 120-fold boost of particle delivery to lungs. The approach is efficient for treatment of pulmonary metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 62 publications
1
128
1
Order By: Relevance
“…Here, we report an erythrocyte hitchhiking platform, ELeCt, consisting of drug-loaded biodegradable NPs assembled on erythrocytes for promoting chemotherapy for effective lung metastasis treatment. Excellent studies have shown NPs hitchhiking on erythrocytes to accumulate in lungs, including recently in metastatic lungs (35); however, the ability of such a mechanism to yield survival benefits has not been known. To that end, we successfully demonstrate the ability of ELeCt to slow down the progression and improve the survival in early-and late-stage experimental melanoma metastasis models, resembling early detection and mid-to-late detection clinical scenarios, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report an erythrocyte hitchhiking platform, ELeCt, consisting of drug-loaded biodegradable NPs assembled on erythrocytes for promoting chemotherapy for effective lung metastasis treatment. Excellent studies have shown NPs hitchhiking on erythrocytes to accumulate in lungs, including recently in metastatic lungs (35); however, the ability of such a mechanism to yield survival benefits has not been known. To that end, we successfully demonstrate the ability of ELeCt to slow down the progression and improve the survival in early-and late-stage experimental melanoma metastasis models, resembling early detection and mid-to-late detection clinical scenarios, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we used Faster R‐CNN for precise quantitative analysis of particle–cell interactions evaluated by the IFC. The developed method can be useful for improvement of the particle efficiency in targeted gene/drug delivery, hyperthermia, magnetic imaging, biosensing, development of smart materials, and other applications . For example, it is possible to determine precisely optimal particle concentration and quantity of carried drugs for reliable cancer cell targeting and killing.…”
Section: Discussionmentioning
confidence: 99%
“…In particular DNA, due to its intrinsic biocompatible, nontoxic and stable properties has been extensively investigated for designing programmable, self-assembling nanostructures for various biomedical applications, such as drug delivery, cellular biosensors and in vivo imaging. In the last years, our laboratory has been involved in the characterization of the structure of truncated octahedral DNA nanocages in silico and in vitro [1][2][3][4][5][6][7] . DNA nanocages are composed by twelve double helices, each one connected to four single stranded linkers, and are fully covalently bound, making the structure highly stable also in biological fluids.…”
Section: Rpc 04mentioning
confidence: 99%